Determinants of University Spin-Offs' Growth: Do Socioeconomic Networks and Support Matter? - Danny Soetanto; Marina van Geenhuizen (European Regional Science Association (ERSA), 2006)
University spin-offs (USOs), as a type of entrepreneurial firms, face the challenge of obtaining sufficient resources to realize perceived business opportunities. USOs are vulnerable to many obstacles in this endeavor, particularly obstacles related to a lack of entrepreneurial knowledge (skills). Support such as office facilities, loan, and business coaching provided by incubator organizations, may help USOs to overcome obstacles. On the other hand, USOs may also overcome the lack of resources by participating in networks of supportive relationships. Social networking by USOs, including its spatial dimension, is not well understood. For instance, it is still not known how universities as a main source of knowledge contribute to the knowledge needs of nearby USOs; similarly, the spatial layout of knowledge relations of USOs has remained virtually unknown. This paper attempts to fill this knowledge gap. Our conceptual model of early growth of USOs, in terms of knowledge needs and fulfilment, is based on resource-based theory and social network theory. In this paper, we assume that USOs' embeddedness in a network of ties is an important source of variation in the acquisition of knowledge resources. We argue that, aside from support from incubation organizations, USOs that maintain networks rich in bridging or boundary-spanning ties with knowledge institutions/actors are better-off compared with USOs that don't employ such ties. We focus on the role of local institutions, particularly the university, as a source of knowledge. Our assumptions are tested on the basis of a sample of academic spin-offs of TU Delft, the Netherlands. The results from regression modeling are expected to support the embeddedness hypothesis and to produce new insights about the link between USOs' social networks, the acquisition of knowledge and survival and growth.
Keywords: 330